IDENTIFICATION OF TRAINING NEEDS ASSESSMENT IN ORGANIZATIONAL CONTEXT - Panji Hidayat Mazhisham; Muhammad Yusuf Khalid; Nik Nadian Nisa Nik Nazli; Ranita Manap; Nur Husna Mohamad Hussain, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Every organization spends money on implementing effective training programmes to maximize the value of their existing human capital. Human development training programmes have been an integral part of encouraging the employees to be a competent and skilled labour force that is knowledgeable and able to perform assigned tasks based on their training needs. Training needs assessment is the first critical stage in training and development. Training needs come from underdeveloped skills, insufficient knowledge or inappropriate employees’ attitudes in their job. Failure to identify the gap between current performance and skills required causes major problems in terms of time, resources, and money, which have been wasted on unnecessary and ineffective training. Therefore, the organization should realize that there are elements for the identification of training needs assessment to increase the knowledge, skills, attitude, and performance of their employees. There is still a lack of study that reviews the potential elements for the identification of the training needs assessment in the organization. This study is conducted to address this gap. Specifically, this study will review previous studies to identify the essential components for the identification of training needs assessment in the organization.